The Role of Games in the Process of Teaching Foreign Languages - Abdurasulovna, Buronova Sevara (International Journal on Integrated Education, 2024)
The article touches upon the topic of using the method of role-playing games / simulations in teaching students’ foreign language. Particular attention is paid to the question of how this method can be used in universities to encourage students to make the most of a foreign language in class. The author draws attention to the fact that the types of role-playing games can be different depending on the level complexity and language skills of students, and that the correct choice is necessary role-playing game corresponding to the level of knowledge of the group. The article demonstrates that role-playing games which are extremely useful and can help students consolidate their knowledge and to teach them a foreign language for professional purposes. Key words: role-playing game (RPG), activity, topic, simulation, basis, development, communication, expressions, facilitator, error correction, misspelled phrases, curriculum, situation, complex, motivation.